2017
DOI: 10.1038/srep41396
|View full text |Cite
|
Sign up to set email alerts
|

Broadband Energy Harvester Using Non-linear Polymer Spring and Electromagnetic/Triboelectric Hybrid Mechanism

Abstract: Over the years, several approaches have been devised to widen the operating bandwidth, but most of them can only be triggered at high accelerations. In this work, we investigate a broadband energy harvester based on combination of non-linear stiffening effect and multimodal energy harvesting to obtain high bandwidth over wide range of accelerations (0.1 g–2.0 g). In order to achieve broadband behavior, a polymer based spring exhibiting multimodal energy harvesting is used. Besides, non-linear stiffening effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
86
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(86 citation statements)
references
References 91 publications
0
86
0
Order By: Relevance
“…[12][13][14][15][16][17][18] And it is found that piezoelectric materials polyvinylidene fluoride (PVDF) has demonstrated to be the largest piezoelectric constants in polymer. [23][24][25] Wang first described a hybrid triboelectric and electromagnetic harvester for the harsh environment. [9] Recently, hybrid nanogenerators have attracted more and more attention.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14][15][16][17][18] And it is found that piezoelectric materials polyvinylidene fluoride (PVDF) has demonstrated to be the largest piezoelectric constants in polymer. [23][24][25] Wang first described a hybrid triboelectric and electromagnetic harvester for the harsh environment. [9] Recently, hybrid nanogenerators have attracted more and more attention.…”
mentioning
confidence: 99%
“…[9] Recently, hybrid nanogenerators have attracted more and more attention. [24] However, the existing research using both electromagnetic and triboelectric method could harvest limited power due to the impedance mismatch. [23] Lee and co-workers reported a broadband nonlinear electromagnetic and triboelectric hybrid energy harvester.…”
mentioning
confidence: 99%
“…[16] While the prior work involves different transduction mechanisms, i.e., electromagnetic and triboelectric, and the volume of active region which is over 100 times larger than the reported device, its power output in resonant mode (50.2 µW) is comparable to the power output (0.6 µW or 0.3 µWrns) reported here given the volume difference. [16] While the prior work involves different transduction mechanisms, i.e., electromagnetic and triboelectric, and the volume of active region which is over 100 times larger than the reported device, its power output in resonant mode (50.2 µW) is comparable to the power output (0.6 µW or 0.3 µWrns) reported here given the volume difference.…”
Section: Introductionmentioning
confidence: 54%
“…[1] (2) A low operating frequency which matches the frequency range of the target vibration sources is needed to obtain maximum efficiency. [11,[14][15][16] Here, we demonstrate a design construct and materials for a soft-rigid hybrid device enabling broadband, resonance tunable vibration energy harvesting and self-powered motion sensing. [10] (3) Broadband response and (4) resonance tunability which can significantly improve the efficiency as most real-world vibrations have widely distributed frequency spectra or time variant frequency peak.…”
mentioning
confidence: 99%
“…Recently, hybrid nanogenerators combining several mechanisms, such as the use of piezoelectric and triboelectric principles to convert mechanical energy into electricity, have been attracting an increasing amount of attention, [10,[18][19][20][21][22][23][24][25][26][27][28][29][30]. Mahmoudi et al reported a multiphysics hybrid piezoelectric-electromagnetic vibration energy harvester with a nonlinear equation of motion for an enhancement power density up to 84% [20].…”
Section: Introductionmentioning
confidence: 99%